1982
DOI: 10.1021/jm00350a006
|View full text |Cite
|
Sign up to set email alerts
|

Potential affinity labels for the opiate receptor based on fentanyl and related compounds

Abstract: Derivatives of fentanyl, 3-methylfentanyl, sufentanil, and lofentanil, possessing chemo- or photoaffinity functionalities, were synthesized as potential affinity reagents for the opiate receptor. Opiate receptor binding constants (IC50) were determined in competition experiments with [3H]naloxone and [3H]naltrexone. Affinity-labeling experiments were generally unsuccessful, although some irreversible attachment was achieved with alpha-diazoamide 17 and aryl azide 23.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Compounds equal in molecular structure to acrylfentanyl have previously been reported in the literature for opiate receptor affinity after synthesis, [36] as a theoretical derivative in mathematic modelling for drug design, [37] and for in vivo activity in mice after custom synthesis. [38] In the latter study, with the use of mouse hot plate tests, it was shown that acrylfentanyl was more potent than fentanyl and had a longer duration of action.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Compounds equal in molecular structure to acrylfentanyl have previously been reported in the literature for opiate receptor affinity after synthesis, [36] as a theoretical derivative in mathematic modelling for drug design, [37] and for in vivo activity in mice after custom synthesis. [38] In the latter study, with the use of mouse hot plate tests, it was shown that acrylfentanyl was more potent than fentanyl and had a longer duration of action.…”
Section: Previous Studiesmentioning
confidence: 99%
“…A number of fentanyl derivatives ( Figure 3) have been synthesized (42). These compounds were generally unsuccessful as affinity labels, although the diazoketone 3 and the arylazide 5 appeared upon photolysis to produce a moderate irreversible inhibition of [3H]naloxone binding to opioid receptors.…”
Section: Photoaffinity Labelsmentioning
confidence: 99%
“…The clinical relevance of in vitro studies at the human opioid receptors cannot be overlooked. Over the past several decades, fentalogs have been pharmacologically characterized primarily in rodent models 24–39 . Much of the fentalog data collected in this area is represented by in vivo experiments in which pharmacokinetic parameters make comparative evaluation difficult.…”
Section: Introductionmentioning
confidence: 99%